Realização profissional, prazer e sofrimento no trabalho e valores:um estudo com profissionais de nível superior - Guimarães, Flavia Arantes Lopes (2005)
The goal of this study was to describe professional accomplishment as part of the pleasure and suffering concept at work and to investigate the impact of the individual and organizational values in the professional accomplishment. The hypothesis was that the individual and organizational values impact favorably for workers' professional accomplishment with university degree. Studies about pleasure, welfare, and psychodynamic of work and theories of the human and organizational values supplied the theoretical foundations for this work. It was developed in two stages. In the first one, it was used Scales of Relative Values to Work, of Organizational Values, of Pleasure-Suffering at Work and records of sociodemographic variables. 178 workers of different companies and several segments got in this study. It demanded the individual s complete superior level and a year of graduation course conclusion. In the second phase 10 workers, which we selected among the first phase individuals, were interviewed individually. The goal in this stage was to describe empirically the phenomenon of the professional accomplishment, under workers' optics. The individuals were selected from the means in pleasure and suffering at work demonstrated in the first phase. Two cases of pleasure factor were chosen, and two of suffering factor, and also two with average results in these factors. The first phase the data were submitted to descriptive statistics, factorial analysis and linear regressions. The interviews were analyzed by content analysis. The group showed pleasure mean above the average point of the scale and mean of suffering down the average point. However, means moderated in Accomplishment and Waste denoted states not characterized as pleasing. High and significant correlations among values at work and organizational values showed equivalence between both. Because of this, only the values related to work entered the regression models to test the main hypothesis of this study. Accomplishment was evaluated as an attitude and not as a value. Eight regressions-standard were done, in which it can be verified that the relative value to the Social Relations in Work was significant predictor of the four pleasure-suffering factors, being directly related to the pleasure factors and inverse to the suffering factors. Of the sociodemographic variables, The Graduation Area was significant and inverse predictor Freedom ; Age predicted significantly Waste and Devaluation In the content analysis, four macro-categories were identified: Factors that interfere in the Professional Accomplishment , Factors that characterize Professional Accomplishment , Characteristics of the Work and Values at Work . The results of this study confirmed that professional accomplishment is at the same time a pleasure source, if it is present, and of suffering, if absent, and that suffered impact of the relative value towards the Social Relations in Work . Three aspects were detected in the search of professional accomplishment: 'Individual's interactions in the social environment and what he seeks in these interactions'; 'Resources to coping with situations which generate suffering at work' and 'dynamic established with organization, in which they are inserted. The results were discussed in the literature light of the area. There were suggested themes for posterior investigations.